EFFECT OF DIFFERENT LATERAL, DRIPPER SPACING AND DRIPPER DISCHARGE RATES ON YIELD AND WUE OF ONION GROWN ON CLAY SOILS - J. M. PATEL,; V. R. NAIK,; R. B. PATEL, (The Bioscan, 2014)
A field experiment with 20 treatment combinations consisting of three levels of lateral spacing (L1: 80 cm, L2: 120 cm, L3: 160 cm), three dripper spacing (D1: 80 cm, D2: 120 cm, D3: 160 cm) and two discharge rates (R1: 4 lph and R2: 8 lph) along with two controls i.e., minisprinkler (MS) and surface control (S) methods of irrigation was conducted using onion as test crop during rabi seasons of 2006-07 and 2007-08 in FRBD with four replications at Soil and Water Management Farm, Navsari Agricultural University, Navsari. The results revealed that closer lateral and dripper spacings gave significantly higher bulb yield of onion as compared to wider spacings. Among the three methods of irrigation, MS had an edge over drip and drip over surface method of irrigation. However, bulb yield recorded under best drip treatment was 29 and 47 per cent more than MS and surface method of irrigation, respectively. The closer lateral spacing resulted in higher WUE (79.88 kg/ha-mm) than wider lateral spacing (56-90 kg/ha-mm). Among the irrigation methods, maximum WUE of 79.85 kg/ha-mm was obtained with MS irrigation and that of minimum with surface method of irrigation (43.04 kg/ha-mm). Within the drip treatments, 80 x 80 cm configuration of drip layout was ranked first by recording higher yield (32.8 t/ha). The corresponding values for minisprinkler method were 25.43 t/ha and for surface method of irrigation 22.38 t/ha.